2023
DOI: 10.3390/nu15040840
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diet and Physical Activity on Psoriasis: A Narrative Review of the Current Evidence

Abstract: Psoriasis is an inflammatory disease with strong genetic links and numerous features of autoimmunity that are also influenced by environment and lifestyle, including nutritional factors and physical activity (PA), with regards to the condition of patients. Recent reports in the field of nutrigenomics indicate a significant impact of nutrients in modulating microRNAs. However, few studies have evaluated the effect of nutritional systems and PA on treating psoriasis. This narrative review updates information reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…As we all know, urticaria is one of the most common skin diseases with high incidence, but the pathogenesis is unclear. However, it has been shown that there is a strong and bidirectional correlation between digestive health and skin health, especially when it comes to homeostasis and allostasis of the skin ( Duchnik et al, 2023 ). Both the skin and the intestine are active immune organs that are constantly exposed to the outside environment ( Coates et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, urticaria is one of the most common skin diseases with high incidence, but the pathogenesis is unclear. However, it has been shown that there is a strong and bidirectional correlation between digestive health and skin health, especially when it comes to homeostasis and allostasis of the skin ( Duchnik et al, 2023 ). Both the skin and the intestine are active immune organs that are constantly exposed to the outside environment ( Coates et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro treatment with apple-derived exosomes displayed anti-inflammatory activity via the promotion of miR-146 expression in human macrophages [ 77 ]. Recently, the potential therapeutic role of quercetin, resveratrol, curcumin, and vitamin D against the psoriasis-related inflammatory and proliferative pathogenetic pathways via miR-155, miR-146, and miR-125b regulation has been described [ 78 ]. The protective action of quercetin in endometriosis has been reported both in vitro and in vivo.…”
Section: Food-derived Nutrients As Mirna Regulators In Chronic Diseasesmentioning
confidence: 99%
“…Also, regular exercise enhances the functioning of the immune system by reducing adiposity and its associated inflammatory inducement. Moreover, exercise has been found to have beneficial effects on mental health, reducing psychological stress, anxiety, and depression [47,48].…”
Section: Exercise and Psoriasismentioning
confidence: 99%